Hubungan Pemakaian Kontrasepsi Suntik dengan Kejadian Amenorea di Wilayah Kerja Puskesmas Atari Jaya Kecamatan Lalembuu Kabupaten Konawe Selatan Tahun 2015 - Wahida, Wahida; Utami, Listyan (Poltekkes Kemenkes Kendari, 2018)
Amenorrhoea is no occurrence of menstruation for 3 months or more in women who have experienced menstrual cycles. Some cases of amenorrhea can be found in injectable contraceptive acceptors. This is confirmed by the data from Southeast Sulawesi province that there are 284,784 and 201,627 (70.8%) among them experiencing amenorrhea. Objective: To find out whether there is a relationship between injectable contraception and the incidence of amenorrhea in the work area of Atari Jaya Health Center, Lalembuu District, South Konawe Regency in 2015. Research methods: Analytical research with design cross-study. The sample in this study amounted to 92 injectable contraceptive acceptors. This research uses an accidental sampling technique. Data analysis included univariate and bivariate analysis using the SPSS (Chi-Square test) program at the level of confidence = 0.05. Amenorrhoea is a complaint that is often felt in injectable contraceptive acceptors. Of the 92 injectable contraceptive acceptors who suffered secondary amenorrhoea, there were 59 (64.1%) acceptors while 33 (35.9%) acceptors did not suffer from secondary amenorrhoea. There is the relationship of injectable contraception with the incidence of amenorrhea. Conclusion: There is a correlation between injectable contraceptive use and the incidence of amenorrhea in the work area of Atari Jaya Community Health Center, Lalembuu Subdistrict, South Konawe Regency in 2015.